2001
DOI: 10.1002/dc.2059
|View full text |Cite
|
Sign up to set email alerts
|

Cultured anaplastic cell lines as immunocytochemistry controls: A comparison of ThinPrep®‐processed smears and conventional air‐dried cytospins

Abstract: Cultured anaplastic cell lines with previously characterized phenotypes are considered to be the best positive controls for immunocytochemistry. We assessed the validity of using anaplastic cell line cytospins as positive controls for immunocytochemistry performed on ThinPrep-processed clinical samples. We compared ThinPrep-processed slides and air-dried cytospins from cultured anaplastic cell lines for intensity and pattern of staining. Also, antigen preservation was assessed over a 3-mo period, using a panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Mitteldorf et al71 reported that TTF‐1 staining intensity was slightly lower in cytopathology preparations than surgical pathology samples, Gong et al40 noted that staining results on cytopathology and tissue samples were comparable with nonnuclear markers and Fadda et al31 described the presence of increased background staining that interfered with interpretation of immunocytochemical stains. A number of authors have described the complex issues surrounding the use of controls,1, 3, 40, 73, 96 while others have clearly described the use of ideal immunocytochemistry controls. Nadji and Ganjei74 included a detailed description of ideal controls when performing immunocytochemical staining in their review of immunocytochemistry in diagnostic cytology in 1990, yet many recently published articles that describe studies utilizing immunocytochemistry include only a vague statement about the controls that were used or no information at all.…”
Section: Discussionmentioning
confidence: 99%
“…Mitteldorf et al71 reported that TTF‐1 staining intensity was slightly lower in cytopathology preparations than surgical pathology samples, Gong et al40 noted that staining results on cytopathology and tissue samples were comparable with nonnuclear markers and Fadda et al31 described the presence of increased background staining that interfered with interpretation of immunocytochemical stains. A number of authors have described the complex issues surrounding the use of controls,1, 3, 40, 73, 96 while others have clearly described the use of ideal immunocytochemistry controls. Nadji and Ganjei74 included a detailed description of ideal controls when performing immunocytochemical staining in their review of immunocytochemistry in diagnostic cytology in 1990, yet many recently published articles that describe studies utilizing immunocytochemistry include only a vague statement about the controls that were used or no information at all.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the storage temperature was set to RT for samples stored in preservation solution, 9,14,16,17 and various temperatures for samples stored on slides. 14,15,18,19 Zappacosta et al 16 investigated whether Thinprep ® -processed samples stored in PreservCyt solution at RT could detect antigens after a long storage period. As a result, phosphorylation of the nuclear transcription factor Stat-5 (pStat-5) was detected for up to 4 months, and nuclear positivity for the proliferation index MIB-1 and membrane positivity for the CD30 antigen was evident for 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that there was no significant loss of immunoreactivity for at least 6 months. Additionally, Wiatrowska et al 15 demonstrated that ThinPrep ® -processed slides stored at À70 C and the air-dried cytospins stored at À70 C retained immunoreactivity for at least 3 months for multiple primary antibodies. The ThinPrep ® -processed slides used in their study were immediately fixed with 95% alcohol, post-fixed with Sprayfix ® , and air-dried.…”
Section: Discussionmentioning
confidence: 99%
“…To further evaluate the impact of cytopreparations on EGFR mutant protein antigenicity, the staining of cell cultures with known mutational status is a useful tool. 11,12 Indeed, in a recent paper by Kawahara et al, 13 EGFR mutated cell lines fixed in SurePath â preservatives performed better when treated by CytoRich Red. However, this paper did not take into account other common cytopreparation methods and did not validate mutationspecific EGFR ICC in samples with a low content of mutated cells or in less than optimal samples.…”
Section: Introductionmentioning
confidence: 99%
“…reported satisfactory results on ethanol‐fixed Papanicolaou‐stained smears. To further evaluate the impact of cytopreparations on EGFR mutant protein antigenicity, the staining of cell cultures with known mutational status is a useful tool . Indeed, in a recent paper by Kawahara et al ., EGFR mutated cell lines fixed in SurePath ® preservatives performed better when treated by CytoRich Red.…”
Section: Introductionmentioning
confidence: 99%